1996
DOI: 10.1046/j.1526-4610.1996.3606352.x
|View full text |Cite
|
Sign up to set email alerts
|

The Placebo Effect in Acute Headache Management: Ketorolac, Meperidine, and Saline in the Emergency Department

Abstract: In a prospective, double-blind, randomized study, ketorolac 60 mg, meperidine 50 mg plus promethazine 25 mg, and normal saline given by intramuscular injection were compared as treatment for acute headache crises. Thirty patients (6 men and 24 women) presenting to an urban emergency department with any type of benign headache were randomized into three groups and filled out the McGill Short-Form Pain Questionnaire with a Pain Rating Index and a Visual Analogue Pain scale. They received one of the study medicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 5 publications
1
32
0
1
Order By: Relevance
“…Symptom red [12] uction is not possible merely by consciously wanting it but can rather be achieved by subconscious belief [11] . In this context, pain and Parkinson's disease are best evaluated where the associated neurobiological effects cannot provide a conclusive explanation, but indicate a rather complex mode of action of placebo effects [13,14] . The involvement of cannabinoids and opioids is considered to be assured because placebo-associated effects can be antagonized by drugs [14] .…”
Section: Discussionmentioning
confidence: 99%
“…Symptom red [12] uction is not possible merely by consciously wanting it but can rather be achieved by subconscious belief [11] . In this context, pain and Parkinson's disease are best evaluated where the associated neurobiological effects cannot provide a conclusive explanation, but indicate a rather complex mode of action of placebo effects [13,14] . The involvement of cannabinoids and opioids is considered to be assured because placebo-associated effects can be antagonized by drugs [14] .…”
Section: Discussionmentioning
confidence: 99%
“…The authors reported that ketorolac was superior to placebo at 0.5 and 1 hour and superior to meperidine at 2 hours (22). Interestingly, these authors had conducted the same study on acute headache crises 2 years earlier and had reported that using all three options could lead to significant pain control, but the amount did not differ among them (23). In a non-interventional non-randomized survey on pain management, intramuscular ketorolac and oral ibuprofen were compared.…”
Section: Discussionmentioning
confidence: 99%
“…6 Other data suggest that ketorolac is at once more expensive and less efficacious than other agents for acute migraine. 5,6 Even the manufacturer's literature shows that 17% of patients who receive ketorolac sustained headache as a side effect.…”
Section: Intravenous Ketorolac Vs Intravenous Prochlorperazine For Thmentioning
confidence: 99%
“…6 Other data suggest that ketorolac is at once more expensive and less efficacious than other agents for acute migraine. 5,6 Even the manufacturer's literature shows that 17% of patients who receive ketorolac sustained headache as a side effect. Thus, there is much accumulated data to suggest that ketorolac is not an optimal first-line agent for headache in the ED, thereby casting doubt on the advisability of the authors' suggestion for further studies of this agent.…”
Section: Intravenous Ketorolac Vs Intravenous Prochlorperazine For Thmentioning
confidence: 99%
See 1 more Smart Citation